2007
DOI: 10.1002/ajmg.a.31877
|View full text |Cite
|
Sign up to set email alerts
|

Bifid tongue: A rare feature associated with infants of diabetic mother syndrome

Abstract: Infants born to diabetic mothers (IDM) are well documented to have a higher rate of congenital malformations. Sacral agenesis/hypogenesis and caudal dysgenesis are classically linked to maternal diabetes, but many other types of anomalies are more frequent. In this case report, we describe a male infant born to a diabetic mother who in addition to other typical congenital abnormalities was born with an impressive bifid tongue. Accompanying congenital anomalies include unilateral microphthalmia, bilateral micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…All these patients did not fissured tongue (0.9%), bifid tongue (0.4%), hairy tongue (0.2%) and macroglossia (0.2%), lingual thyroid nodule (0.1%). Infants born to diabetic mothers are well documented to have a higher rate of congenital malformations (James et al, 2007;Bhuiyan et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…All these patients did not fissured tongue (0.9%), bifid tongue (0.4%), hairy tongue (0.2%) and macroglossia (0.2%), lingual thyroid nodule (0.1%). Infants born to diabetic mothers are well documented to have a higher rate of congenital malformations (James et al, 2007;Bhuiyan et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Bifid tongue was seen in 5 out of 16 OFD1 mutation positive patients [Thauvin‐Robinet et al, 2006]. A literature search performed by James et al [2007] revealed that bifid tongue has also been reported in infants of diabetic mothers, hyperimmunoglobulin E syndrome, trisomy 7 mosaicism, short rib‐polydactyly syndrome type IV (Beemer–Langer syndrome [OMIM 269860]), fibrochondrogenesis [OMIM 228520], and in association with cleft palate and Klippel–Feil anomaly. In the OPD2 literature, bifid tongue has only been described once before [Verloes et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…[10–13] Bifid tongue has also been reported as a rare feature associated with infants of diabetic mother syndrome. [14] Literature also gives a reference of bifid tongue as a complication of tongue piercing. [15] Associations have also been postulated with cleft palate, mandibular cleft, midline palatomandibular bony fusion and cervical vertebrae.…”
Section: Discussionmentioning
confidence: 99%